Answer: C. K= 2.5
Step-by-step explanation:
Isolate the variable by dividing each side by factors that don't contain the variable.
M2p÷3
3(2)(6)÷3
3 (2)=6
6 (6)÷3
6×6=36
36÷3=12
The expression m2p÷3 equals 12
Answer:
divide .
Step-by-step explanation:
Lets set the two numbers as 'a' and 'b'
Now let us set up some equations based on the information:
- sum of two numbers 49 --> a + b = 49
- difference of the two numbers is 15 --> a -b =15
Equations
a + b = 49 -- equation 1
a - b = 15 -- equation 2
Solve:
(equation 1) + (equation 2)
2a = 64
a = 32 -- equation 3
(equation 3)'s value of a into (equation 2)
32 - b = 15
b = 17
The products of 'a' and 'b' is 544
Hope that helps!
The other endpoint would have to be (-5,2), going off the definition of a midpoint. Since 3 is for units to the right of -1, that would mean that the other end point would have to be 4 units to the left, which is -5.